Education On Handling Acute Phase Sports Injuries In Students At High School N 13 Jambi City - Putra Hadi Hadi; Indah Permata Sari (CV Media Inti Teknologi, 2025)
This community service program aims to increase students' knowledge and awareness about handling acute sports injuries. The targets of this program are students of SMA N 13 Jambi City who are actively involved in physical activities and school sports. The scope of activities includes identifying the types of acute sports injuries that commonly occur, understanding the symptoms, and introducing fast and proper first aid techniques using the RICE (Rest, Ice, Compression, Elevation) method. The methods applied in this program consist of educational seminars, interactive discussions, demonstrations, and hands-on practice sessions. The activities were conducted directly in schools and involved both theoretical and practical components to ensure better understanding and engagement. The results showed a significant increase in the students' knowledge level, as indicated by the comparison between the pre-test and post-test scores, the pre-test score was 36.02%, while the average post-test score increased significantly to 93.35%. The paired t-test analysis showed a t-value = -38.355 with a p-value = 0.000 (p < 0.05), meaning the difference was statistically significant. This proves that providing hands-on education through lectures, discussions, and simulations is effective in improving students' knowledge of acute-phase sports injury management. Participants demonstrated increased confidence and accuracy in identifying and responding to acute injury scenarios. In conclusion, this educational intervention successfully increased students' awareness and preparedness in managing acute sports injuries, highlighting the importance of early and appropriate treatment to prevent further complications. The program is expected to make a positive contribution to injury prevention and health promotion among secondary school students involved in sports.